The economic development and the emergence of the quaternary sector: New evidence of Japan - Xuchong Yan (New Applied Studies in Management, Economics & Accounting, 2025)
This study analyzed the limitations of the three-industry structure and the concept and existence of the quaternary sector through a literature review, and then examined the development status of the quaternary sector in Japan through case analysis, contributing to the existing literature. Through the above analysis, this study found that: 1) The traditional three-industry structure can no longer explain the new industries that have emerged with the development of technology. It is imperative to consider new theories and methods for analyzing these new industries; 2) The quaternary sector is a knowledge-dependent service sector distinct from the tertiary sector. With the development of the Fourth Industrial Revolution, new technologies have been introduced, leading to the emergence of the quaternary sector. Technological innovation, such as the development and improvement of technology, is a crucial factor in the emergence of the quaternary sector; 3) Japan's quaternary sector has exhibited a slow growth trend. The fastest-growing sectors are professional, scientific, and technical activities, and information and communications. Financial and insurance activities showed a trend of faster growth in the early stage and slower growth in the later stage. Education has developed relatively steadily. Additionally, in economically developed regions, such as the Kanto region, the Tokai region, the Kinki region, and the Kyushu region, the quaternary sector is developing rapidly.